Modulating donor mitochondrial fusion/fission delivers immunoprotective effects in cardiac transplantation. Issue 2 (8th November 2021) - Tran, Danh T.; Tu, Zhenxiao; Alawieh, Ali; Mulligan, Jennifer; Esckilsen, Scott; Quinn, Kristen; Sundararaj, Kamala; Wallace, Caroline; Finnegan, Ryan; Allen, Patterson; Mehrotra, Shikhar; Atkinson, Carl; et al.
Abstract : Early insults associated with cardiac transplantation increase the immunogenicity of donor microvascular endothelial cells (ECs), which interact with recipient alloreactive memory T cells and promote responses leading to allograft rejection. Thus, modulating EC immunogenicity could potentially alter T cell responses. Recent studies have shown modulating mitochondrial fusion/fission alters immune cell phenotype. Here, we assess whether modulating mitochondrial fusion/fission reduces EC immunogenicity and alters EC‐T cell interactions. By knocking down DRP1, a mitochondrial fission protein, or by using the small molecules M1, a fusion promoter, and Mdivi1, a fission inhibitor, we demonstrate that promoting mitochondrial fusion reduced EC immunogenicity to allogeneic CD8 + T cells, shown by decreased T cell cytotoxic proteins, decreased EC VCAM‐1, MHC‐I expression, and increased PD‐L1 expression. Co‐cultured T cells also displayed decreased memory frequencies and Ki‐67 proliferative index. For in vivo significance, we used a novel murine brain‐dead donor transplant model. Balb/c hearts pretreated with M1/Mdivi1 after brain‐death induction were heterotopically transplanted into C57BL/6 recipients. We demonstrate that, in line with our in vitro studies, M1/Mdivi1 pretreatment protected cardiac allografts from injury, decreased infiltrating T cell production of cytotoxic proteins, and prolonged allograft survival. Collectively, our data show promoting mitochondrial fusion in donor ECs mitigates recipient T cell responses and leads to significantly improved cardiac transplant survival. Abstract : Therapeutic promotion of endothelial mitochondrial fusion reduces allo‐reactive T‐cell responses and improves cardiac allograft survival. Mullan comments on page 337 .